Metode Membentuk Kesehatan Mental Siswa Melalui Kegiatan Ice Breaking - I Gusti Ayu Adi Rahayuni (Jayapangus Press, 2020)
Students' mental healt has decreased as a result of stress, depression, lack of rest time and high learning load. Then the best method is needed to reduce the poor of students' mental healt. Ice breaking is one of the methods in building students' mentality. The purpose of this study is to find out the right ice breaking technique in an effort to grow student mentality and the benefits of the application of ice breaking. In Technique Data analysis, used techniques with qualitative descriptive analysis. The conclusion of this study is, ice breaking is one of method that can be used to help the mental build of students so that students can follow the learning process with enthusiasm, fun and mentality of students formed properly.